The Relationship of Nursing Teamwork and Job Satisfaction in Hospitals - Helga Bragadóttir RN, PhD, FAAN; Beatrice J. Kalisch RN, PhD, FAAN; Birna G. Flygenring RN, MSc; Gudný Bergthóra Tryggvadóttir MSc (SAGE Publishing, 2023)
Introduction Teamwork is identified as a key contributor to patient safety and good teamwork is recognized as one of the presumptions of healthy work environment in nursing. The importance of job satisfaction in nursing has repeatedly been confirmed, but only recently has the association of job satisfaction and nursing teamwork been identified. Objective To identify the level of nursing teamwork in hospitals in Iceland and its relationship with job satisfaction. Methods This was a quantitative descriptive cross-sectional study. Data were collected with the Nursing Teamwork Survey administered to nursing staff in medical, surgical, and intensive care units in hospitals in Iceland. This study is based on data from 567 participants. Results A logistic regression analysis indicated that work experience on current unit and perceived staffing adequacy contributes to job satisfaction and when controlling for unit type, role, experience on current unit and staffing adequacy, those reporting better teamwork are significantly more likely to be satisfied with their current position. With an additional unit for overall nursing teamwork, participants are almost five times likelier to be satisfied with their current position. Conclusion Study findings show that there is a significant relationship between nursing teamwork and job satisfaction. The findings of this study confirm the importance of adequate staffing and good teamwork for nurses' job satisfaction. Staffing however, will remain the most challenging part of the equation as lack of nursing staff is foreseen globally in the coming decades turning the spotlight to teamwork. All stakeholders, including clinical nurse leaders, administrators, and instructors, need to emphasize on strengthening nursing teamwork. Good teamwork with increased job satisfaction may prevent turnover and shortage of nurses, an issue expected to grow during and following the COVID-19 pandemic. Facilitating good teamwork should be one of the priorities of every nurse leader.